1991
DOI: 10.1677/joe.0.1280021
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone-related protein in milk and its correlation with bovine milk calcium

Abstract: Parathyroid hormone-related protein (PTHrP) has been shown to be present in milk of various mammals. We have assayed PTHrP in milk of various species by radioimmunoassay and estimated the molecular weights by Western blot analysis. PTHrP concentrations in bovine, ovine and human milk were 59.2 +/- 18.5, 74.1 +/- 35.0 and 36.6 +/- 20.7 micrograms/l (mean +/- S.D.) respectively, in pooled samples collected at various stages of lactation. PTHrP in mammalian milk was found to exist in two forms with molecular weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 16 publications
2
36
0
2
Order By: Relevance
“…A significant increase in the concentration of PTHrP established in our study in early lactation is in agreement with the study conducted by Lippuner et al (1996) in humans, in which significantly higher PTHrP values were observed in the blood of lactating women than in that of nonlactating ones. The results of our study are probably connected with the role of PTHrP in the mammary gland during lactation, which is assumed to promote calcium transport in milk (Law et al, 1991;Barlet et al, 1992). However, Onda et al (2006) did not establish significant arterial-venous differences in the blood concentration of PTHrP upstream and downstream of the mammary gland as evidence of the release of PTHrP from the mammary gland, possibly as a result of the very low PTHrP concentrations in both arterial and venous blood, which were below the detection limit in their respective tests.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…A significant increase in the concentration of PTHrP established in our study in early lactation is in agreement with the study conducted by Lippuner et al (1996) in humans, in which significantly higher PTHrP values were observed in the blood of lactating women than in that of nonlactating ones. The results of our study are probably connected with the role of PTHrP in the mammary gland during lactation, which is assumed to promote calcium transport in milk (Law et al, 1991;Barlet et al, 1992). However, Onda et al (2006) did not establish significant arterial-venous differences in the blood concentration of PTHrP upstream and downstream of the mammary gland as evidence of the release of PTHrP from the mammary gland, possibly as a result of the very low PTHrP concentrations in both arterial and venous blood, which were below the detection limit in their respective tests.…”
Section: Discussionsupporting
confidence: 61%
“…During lactation, PTHrP is presumed to have a local role in the regulation of calcium transport in milk and a systemic role in the adaptation to lactation (Bromage and DeLuca, 1985). In cows, a positive correlation has been found between PTHrP and calcium levels in milk (Law et al, 1991). Barlet et al (1992) observed an increased calcium concentration in the milk of lactating goats after the administration of human PTHrP (1-34) and (1-86).…”
mentioning
confidence: 99%
“…The intense expression of PTHrP in lactating mammary tissue, and its secretion into milk at high concentrations, have prompted investigations to determine whether PTHrP regulates the calcium content of milk. Early studies showed that the PTHrP concentration in milk was positively correlated with calcium content of milk from cows (539,681) and rats (989), but not in all studies from rats (738,1004). One study found that with time since suckling, PTHrP content of milk decreased while the calcium content increased (1004).…”
Section: Animal Datamentioning
confidence: 99%
“…5B). Interestingly, various isoforms of PTHLH have been identified in human milk (26), which were detected with varying intensities between donors.…”
Section: Milk-derived Ev Contain Proteins Not Listed In the Vesiclepementioning
confidence: 99%